2000
DOI: 10.1055/s-2000-8808
|View full text |Cite
|
Sign up to set email alerts
|

Zur Anatomie der Venenklappen der V. jugularis interna

Abstract: The present study demonstrates the variety of the valves of the jugular vein. They play an important role to impede the retrograde flow during cardiopulmonary resuscitation as well as in jugular vein cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…IJV valves have been visualized in most patients examined and are located approximately 2–2·5 cm cephalad to the IJV–subclavian junction 5,14. Autopsy studies revealed the presence of IJV valves in 93–100% of subjects (Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…IJV valves have been visualized in most patients examined and are located approximately 2–2·5 cm cephalad to the IJV–subclavian junction 5,14. Autopsy studies revealed the presence of IJV valves in 93–100% of subjects (Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…In our observations of the FV, bicuspid valves predominated while monocuspid and tricuspid valves were occasional, which accords with Basmajian's findings (Basmajian, 1951). Most venous valves are bicuspid; mono-and tri-cuspid valves are rarer (Powell and Lynn, 1951;Staubesand and Rulffs, 1958;Dresser and McKinney, 1987;Harmon and Edwards, 1987;Miyake et al, 1996;Sanchez-Hanke et al, 2000;Celepci and Brenner, 2011). The presence and abundance of mono-and tri-cuspidity not only varies among venous systems, possibly depending on physical interactions with the surrounding tissues (Sanchez-Hanke et al, 2000), but also in the same venous system among populations.…”
Section: Valve Topography and Abundancementioning
confidence: 99%
“…Most venous valves are bicuspid; mono-and tri-cuspid valves are rarer (Powell and Lynn, 1951;Staubesand and Rulffs, 1958;Dresser and McKinney, 1987;Harmon and Edwards, 1987;Miyake et al, 1996;Sanchez-Hanke et al, 2000;Celepci and Brenner, 2011). The presence and abundance of mono-and tri-cuspidity not only varies among venous systems, possibly depending on physical interactions with the surrounding tissues (Sanchez-Hanke et al, 2000), but also in the same venous system among populations. Comparative fluidstructure interactions in virtual mono-, bi-and tricuspid venous valve models suggest that mechanical stress via shear force and wall pressures is lowest in bicuspid models (Chen et al, 2014).…”
Section: Valve Topography and Abundancementioning
confidence: 99%
“…A valve is present in the IJV at the junction with the subclavian vein. This valve may be bicuspid or tricuspid and is commonly located approximately 2 cm above the junction with the brachiocephalic vein (Sanchez-Hanke et al, 2000). A study of the IJV valve in cadaveric and live human subjects demonstrated the same valve location, mostly bicuspid, and also reported that only 7% of valves were incompetent out of 41 valves tested (Silva et al, 2002).…”
Section: The Cerebrospinal Venous System In Relation To Ccsvimentioning
confidence: 99%